Manejo anti resistencia de la cenicilla (Oidium sp) en el cultivo del rosal (Rosa sp.), bajo condiciones de invernadero. - Quezada Loor, Washington Orlando (2017)
SUMMARY This research aims to determine the anti powdery mildew resistance management of rosebush with different active ingredients and mechanisms of action of fungicides. The study area is located in the Naples meeting sector parish Ayora, Canton Cayambe, Pichincha province, with 0 ° 03'31.09 geographical coordinates "north latitude and 78 ° 08'53.93" west longitude at an altitude of 2802 meters above sea level. The objectives were to identify the proper rotation of fungicides by anti resistance of each of the treatments handling, evaluate performance and agronomic performance of crop rose against fungicide application and analyze cost benefits with the best control strategy fungicides. Seven treatments by combining seven fungicide rotations performed every five days and a sulfur- based witness was investigated. the Complete Random Design (DCA) was used with 8 treatments and three repetitions, giving a total of 24 experimental units. The total area of the experiment was 324.18 m2, 14.62 m2 plots with a useful area of 2.43 m2. , Percentage of disease incidence, severity percentage of powdery mildew of rose, effectiveness, size stems to harvest, along the flower bud number of export and domestic flowering stems per m2 was evaluated. Data analysis of variance and underwent treatment comparison hiso with Duncan test 5%. The results determined that the cultivation of the rose variety Tara, responded favorably to the application of the rotation of fungicides used different mechanisms of action. Treatments applying fungicides rotation different mechanisms of action, with favorable results compared to the control treatment based on sulfur. The lowest percentage of incidence and severity as well as greater efficiency during the rotation cycle of fungicides which was maintained for the productive development of the crop, introduced handling anti resistance Metrafenone - Albesilate - Bupirimate - Strobilurin - triflumizole - spiroxamine - Sulphur . The largest number of stems export as an important part of growing business rose presented it treat anti-resistance management Metrafenone fungicides - Albesilate - Bupirimate - Strobilurin - triflumizole - spiroxamine - Sulphur; and higher yield per unit area in export presented it stems treatment with the rotation of fungicides Metrafenone - Albesilate - Bupirimate - Strobilurin - triflumizole - spiroxamine - Sulphur.